The New Role of Labor Unions in the AI Era - Arenas Falótico, Andrés J.; Bayón Pérez, Jessica (IGI GLOBAL, 2026)
As artificial intelligence (AI) is introduced on a day-to-day basis, its use as tool is an effective and transformative tool for companies and even labor unions. As AI reshapes industries, tasks, and redefine jobs, unions must adapt to compete with its implementation. Traditionally, unions negotiate wages and working conditions, now they are fighting for job security and worker presentation with the introduction of AI. This new role positions labor unions as crucial mediators between technological innovation and worker rights, ensuring that AI benefits all, rather than deepening inequality. The New Role of Labor Unions in the AI Era explores the transformative role of AI and how it is affecting the field of business and management. It further discusses how technologies are reshaping business strategies, operations, and the overall management landscape. Covering topics such as automation, labor markets, and workplace harassment, this book is a useful resource for researchers, academicians, students, and more.
Keywords: inteligencia artificial; representación colectiva; automatización; sindicalismo; sindicalismo digital; economía colaborativa; cultura organizacional; salud mental; mercado laboral; sindicato; transformación digital